Ideologija lastništva in (re)produkcija neenakosti - Ploštajner, Klemen (Socialno delo, 2016)
Western societies have in the recent years become societies of homeowners. This is the product of state policies of privatization of social housing, promotion of home ownership and neglect of rental market. These kinds of policies are based on the assumption that home ownership is the most desirable, highest and the right form of solving the housing question. The upgrade of policies that promote home ownership are practices of bonding social rights on assets, which literature calls "asset-based keynesianism". This state necessarily leads to the exclusion and reinforcement of inequalities between citizens on different locations, between different generations and mostly between those who have the access to assets and those who do not have this privilege. With strengthening of financialization, commodification of housing, concentration of demand because of uneven development in capitalism and privatization of common wealth, housing market is becoming one of the key places of not only reproduction, but also production of inequality. The article focuses on the role that home ownership plays in the creation and reinforcement of inequality. It also looks at the way state policies not only promote home ownership, but also use it as a tool for privatization of state social roles.
Keywords: housing; lastništvo; neenakost; neoliberalism; stanovanja; housing policy; neoliberalizem; commodification; stanovanjska politika; market; trg